2007
DOI: 10.1542/peds.2006-2401
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae and Atypical Stevens-Johnson Syndrome: A Case Series

Abstract: Mycoplasma pneumoniae is a common cause of community-acquired respiratory illness in the adolescent population. Stevens-Johnson syndrome is an extrapulmonary manifestation that has been associated with M. pneumoniae infections. Three adolescent males presented within a 1-month period with M. pneumoniae respiratory illnesses and severe mucositis but without the classic rash typical of Stevens-Johnson. Diagnosis was facilitated by the use of a polymerase chain reaction-based assay. This case series highlights th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 13 publications
1
56
0
2
Order By: Relevance
“…3 There have been several case reports in which Mycoplasma infection is localized to the mucous membranes with very little to no skin involvement. [4][5][6] Patients will often have ocular, oral, and genital involvement as in our patient. This was previously known as atypical SJS but it has been suggested that the term Mycoplasma pneumoniaeassociated mucositis would be a more appropriate definition.…”
Section: Discussionmentioning
confidence: 64%
“…3 There have been several case reports in which Mycoplasma infection is localized to the mucous membranes with very little to no skin involvement. [4][5][6] Patients will often have ocular, oral, and genital involvement as in our patient. This was previously known as atypical SJS but it has been suggested that the term Mycoplasma pneumoniaeassociated mucositis would be a more appropriate definition.…”
Section: Discussionmentioning
confidence: 64%
“…7 SJS was classically ascribed to a medication hypersensitivity reaction; however, infectious etiologies, including Mycoplasma pneumoniae (Mp), are increasingly recognized as inciting agents. [8][9][10] SJS has an estimated incidence of 1 to 7 cases per million person-years, [11][12][13][14][15] although pediatric rates are not well described because of a lack of published information. Epidemiologic clusters of SJS are exceptionally rare and have been associated with both medications (including mebendazole and metronidazole) 16 and infection such as Mp.…”
Section: Stevens-johnson Syndrome (Sjs) Ismentioning
confidence: 99%
“…Epidemiologic clusters of SJS are exceptionally rare and have been associated with both medications (including mebendazole and metronidazole) 16 and infection such as Mp. 9,17,18 SJS attributed to Mp represents only a small fraction of overall cases, and published information about the clinical characteristics of this condition is limited to small case series.…”
Section: Stevens-johnson Syndrome (Sjs) Ismentioning
confidence: 99%
See 1 more Smart Citation
“…In children, M. pneumoniae is also the most commonly-identified infectious cause of StevensJohnson syndrome. Classic rash and mucosal involvement accompany the signs and symptoms of an M. pneumoniae respiratory infection [47]. It can also cause urticaria, toxic epidermal necrolysis and pityriasis rosea [8,15].…”
Section: Dermatological Manifestationsmentioning
confidence: 99%